2019
DOI: 10.1155/2019/5157024
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Autonomic Nervous System on Cardiac Rhythm during the Evolution of Diabetes Mellitus Using Heart Rate Variability as a Biomarker

Abstract: Heart rate variability (HRV) is highly influenced by the Autonomic Nervous System (ANS). Several illnesses have been associated with changes in the ANS, thus altering the pattern of HRV. However, the variability of the heart rhythm is originated within the Sinus Atrial Node (SAN) which has its own variability. Still, although both oscillators produce HRV, the influence of the SAN on HRV has not yet been exhaustively studied. On the other hand, the complications of diabetes mellitus (DM), for instance, nephropa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…However, after a time period equivalent to 15 human years of DM induction without hypoglycemic treatment CAN, a decrease in HRV is developed (Figure 6). Additionally, in this second stage, mice showed denervation in the pacemaker tissue [13]. We conclude that the use of HRV and Poincaré plots could detect CAN even in early stages of the disease, and therefore it will allow introducing therapeutic maneuvers to control the symptoms and delay the damage to the ANS due to DM.…”
Section: Diabetes Mellitusmentioning
confidence: 73%
See 1 more Smart Citation
“…However, after a time period equivalent to 15 human years of DM induction without hypoglycemic treatment CAN, a decrease in HRV is developed (Figure 6). Additionally, in this second stage, mice showed denervation in the pacemaker tissue [13]. We conclude that the use of HRV and Poincaré plots could detect CAN even in early stages of the disease, and therefore it will allow introducing therapeutic maneuvers to control the symptoms and delay the damage to the ANS due to DM.…”
Section: Diabetes Mellitusmentioning
confidence: 73%
“…The width or SDD 1 will be used to determine the variability of D1; this parameter is related to the short-term variability of the RR, and this relates to the interaction of the sympathetic system and the heart. To calculate SDD 1 all distances from points to the identity line are calculated the average and standard deviation [3,13]. Thus it is found that…”
Section: Sdd 1 and Sdd 2 Calculationmentioning
confidence: 99%
“…Heart rate variability and leukocytes are associated in the context of metabolic diseases 16 , 17 . However, the relationship between RHR and different leukocyte subgroups in obesity is still unclear.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have demonstrated an inverse association of weight gain and obesity with alteration of HRV parameters [ 27 , 28 , 29 ]. There are various determinants which can influence HRV in individuals with obesity including, e.g., co-morbidities, dietary habits, physical activity, emotional stress, and genetic factors [ 5 , 30 , 31 , 32 ].…”
Section: Heart Rate Variability In Individuals With Obesitymentioning
confidence: 99%